Efficiency as the Missing Link: Exploring How ESG Practices Shape Cash Holding Decisions - Puput Tri Komalasari; Patrik Alessandro Hoya; Ballav Niroula (Jurnal Ilmu Manajemen, 2026)
This study examines the relationship between environmental, social, and governance (ESG) performance and corporate cash holdings by investigating the mediating role of firm efficiency among Indonesian non-financial firms from 2018 through 2022. Using 405 firm-year observations and a mediation-based panel regression analysis, we address the ongoing debate regarding whether ESG practices reduce or increase firms’ incentives to retain cash. The findings reveal that, while ESG performance does not directly affect corporate cash holdings, it significantly improves firm efficiency, and this improvement subsequently has a significant positive effect on cash holdings, indicating full mediation. Thus, ESG practices indirectly influence corporate liquidity policy by enhancing operational capability rather than solely through direct governance effects. More importantly, the positive relationship between firm efficiency and cash holdings indicates that operationally efficient firms tend to maintain large cash reserves as a form of strategic financial flexibility, so these cash reserves are not necessarily evidence of agency problems or inefficient resource allocation. In the context of emerging markets such as Indonesia’s, where external financing conditions remain relatively costly and volatile, efficient firms may intentionally accumulate cash to support sustainability investments, maintain resilience, and mitigate future financing constraints. This study contributes to the ESG-finance literature by highlighting the role of firm efficiency as an important transmission mechanism linking ESG practices and corporate liquidity policy, and it also provides evidence that cash holdings in emerging markets may reflect strategic preparedness and internal financing capacity rather than managerial opportunism.